Factors associated with progression and sex-specific patterns in chronic subdural hematoma: a single-centre retrospective study - Yang, Weijian; Du, Zhuoying; Chen, Qifang; Yuan, Qiang; Fu, Pengfei; Fang, Jiang; Hu, Jin; Wu, Gang (Frontiers in Neurology, 2025)
ObjectiveThis study aims to identify determinants of chronic subdural hematoma (CSDH) progression and to evaluate potential sex-related differences.MethodsPatients with unilateral CSDH were retrospectively enrolled between January 2018 and December 2024. Data on demographics, clinical characteristics, hematoma density, hematological parameters and coagulation function were collected. Multivariable logistic regression was used to identify independent predictors. Patients were randomly divided into training and validation cohorts in a 7:3 ratio to identify factors associated with hematoma progression. Subsequently, logistic regression models were applied to both cohorts to confirm the factors influencing progression.ResultsThis retrospective study enrolled 1,142 patients, who were categorized into progression (n = 773, 67.69%) and recovery (n = 369, 32.31%) groups. Multivariate regression analysis revealed that international normalized ratio (INR) (OR 7.39, 95% CI 2.79–19.55), hypertension (OR 5.35, 95% CI 2.80–10.25), diabetes (OR 4.68, 95% CI 1.74–12.60), neutrophil to lymphocyte ratio (NLR) (OR 2.14, 95% CI 1.46–3.13), white blood cell count (WBC) (OR 1.16, 95% CI 1.02–1.31), and maximum hematoma density (MaHD) (OR 1.02, 95% CI 1.01–1.03) were independent risk factors for hematoma progression, whereas female gender (OR 0.61, 95% CI 0.40–0.95) was identified as a protective factor against CSDH progression. Subgroup analysis stratified by sex revealed statistically significant differences between female and male patients in hemoglobin concentration, serum albumin level, and platelet count. Nevertheless, all values remained within the respective sex-specific reference intervals.ConclusionElevated INR, hypertension, diabetes, NLR, WBC, and MaHD were independently associated with CSDH progression. Female sex conferred a protective effect. These findings require prospective validation.